2015
DOI: 10.1016/j.apcatb.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic microwave pyrolysis of waste engine oil using metallic pyrolysis char

Abstract: a b s t r a c tMicrowave pyrolysis was performed on waste engine oil pre-mixed with different amounts of metallicchar catalyst produced previously from a similar microwave pyrolysis process. The metallic-char catalyst was first prepared by pretreatment with calcination followed by analyses to determine its various properties. The heating characteristics of the mixture of waste oil and metallic-char during the pyrolysis were investigated, and the catalytic influence of the metallic-char on the yield and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(49 citation statements)
references
References 50 publications
(126 reference statements)
0
47
0
2
Order By: Relevance
“…Significantly, the deactivated catalysts could be much easier renewed and regenerated. So far, many types of catalysts have been used for the catalytic pyrolysis of oily wastes [20][21][22][23][24]. Lam et al [21] also found that the metallic pyrolysis char could be used for waste engine oil upgrading by catalytic microwave pyrolysis.…”
Section: Introductionmentioning
confidence: 98%
“…Significantly, the deactivated catalysts could be much easier renewed and regenerated. So far, many types of catalysts have been used for the catalytic pyrolysis of oily wastes [20][21][22][23][24]. Lam et al [21] also found that the metallic pyrolysis char could be used for waste engine oil upgrading by catalytic microwave pyrolysis.…”
Section: Introductionmentioning
confidence: 98%
“…The alkanes in the pyrolysis oil were found to decrease with the increase of the pyrolysis temperature. This could be accounted for by the increased occurrence of secondary reactions such as dehydration, aromatization and decarboxylation at higher temperatures during the pyrolysis process, converting the alkanes into alkenes or aromatic compounds [10,18]. …”
Section: Temperature Profile and Heating Performance During Microwavementioning
confidence: 99%
“…The volatiles are comprised of gaseous hydrocarbons, light hydrocarbons (<C 25 ) and permanent gases such as CO and H 2 . In the secondary pyrolysis stage, enhanced cracking and heterogeneous reactions could occur to produce lighter gaseous hydrocarbons (C 1 -C 4 ), liquid oil hydrocarbons (<C 18 ) and some other gas species [10]. In addition, various types of reactions such as deoxygenation, aromatization, dehydrogenation and reforming could occur and influence the product yield and compositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave radiation as a heat source provide rapid and targeted heating to the inside waste palm shell by dipole rotation and ionic conduction [10]. The study also examined the influence from varying the amount of waste palm shell as feedstock and the pyrolysis temperature on the process features, the yield and composition of the WPSAC obtained, and its adsorption of methylene blue.…”
Section: Introductionmentioning
confidence: 99%